2004
DOI: 10.1016/j.femsle.2004.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Genome diversity among regional populations of Francisella tularensis subspecies tularensis and Francisella tularensis subspecies holarctica isolated from the US

Abstract: Francisella tularensis is a highly infectious facultative intracellular pathogen that is considered a potential agent of bioterrorism. Four different F. tularensis subspecies have been identified and they appear to display different ecological and virulence characteristics as well as differences in geographical distribution. One simple explanation for the variation in ecological and virulence characteristics is that they are conferred by differences in genome content. To characterize genome content among stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…Although recent comparative genomic analyses have begun to demonstrate genetic differences among the subspecies, these alone have been insufficient to explain their relative virulence (2,14,21,28). It was recently shown that sublethal infection of mice with F. tularensis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent comparative genomic analyses have begun to demonstrate genetic differences among the subspecies, these alone have been insufficient to explain their relative virulence (2,14,21,28). It was recently shown that sublethal infection of mice with F. tularensis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures for this study were propagated on chocolate agar at 37°C in 5% CO 2 . Glycerol fermentation was tested in a limited number of isolates, either as described previously (26) or by using Biolog (Biolog, Inc., Hayward, CA) according to the manufacturer's instructions. A summary of spatial, temporal, host, and other pertinent demographic information, as well as prior subspecies determinations of all strains and/or DNA used in this study, is listed in Table S1 in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
“…tularensis and has apparently been lost from the F. tularensis subsp. holarctica genome (4,26). Comparative genome-sequencing efforts are also under way and promise to provide detailed information with regard to specific strains.…”
mentioning
confidence: 99%
“…c Region of difference independently identified by Samrakandi et al (21). RD18 and RD19 correspond to L3 and L2, respectively.…”
mentioning
confidence: 96%